HUBUNGAN KEPEMIMPINAN KHARISMATIK KEPALA SEKOLAH TERHADAP KINERJA GURU SD MUHAMMADIYAH 3 - Syifa Min Zaytun, Salwa; Bambang Irawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the lack of charismatic leadership of the principal which results in teachers not showing maximum performance. The purpose of this study is to determine how big the Relationship between Charismatic Leadership of the Principal and Teacher Performance is. This research method is a correlative cause-and-effect method with a quantitative approach. The sampling technique is by random sampling, the data collection technique uses questionnaires and documentation instruments. The population and sample are 1 Principal and 23 Teachers of Muhammadiyah Elementary School 3. The results of the study of Charismatic Leadership of the Principal and Teacher Performance show a relationship and the relationship is 73.6%.